GOVERNMENT™S PERFORMANCE ON THE PUBLIC SERVICE REGARDING BUILDING PERMITS IN URBAN PLANNING OFFICE OF GORONTALO CITY - Sulila, Ismet; Wolok, Tineke (Journal of Community Research and Service, 2018)
Abstract Government™s performance in the public service regarding building permit in Urban Planning Department of Gorontalo City. This research aims at investigating the public service performance at the Urban Planning Office of Gorontalo city. This qualitative descriptive research employed observation, interview, and documentation in collecting the data. The technique of data analysis comprised of data reduction, data display, and conclusion. The results reveal that the government™s performance is influenced by 1) human resources, 2) facilities and infrastructures, and 3) job mechanism. Furthermore, the efforts to improve the performance are 1) participation of the officers in technical training about building permits policy; 2) disseminating the insight regarding building permit on the district level through the media such as newspaper, television, and radio; 3) providing proper facilities and infrastructures. Efforts to improve the performance should include 1) upgrading human resources; 2) providing facilities and infrastructures; 3) coordinating with the local government unit; 4) promoting awareness of the society since some people do not have a properunderstanding of the legality of building permits. Keywords: Performance and Public Services